Creating Future Leader through Creative Minority Vision on Higher Education (A Case Study on SWCU) - Listyanto Aji Nugroho; Sariyatun Sariyatun; Suryo Ediyono (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Higher Education has a key role in preparing society to entering the era of Society 5.0. Higher education must be able to change the paradigm of society with good ideas and thoughts towards a better social order. Apart from knowledge, higher education must be able to form a generation of change agents in society. This study aims to find out more about the vision of the Satya Wacana Christian University to form a generation of leaders with a “creative minority” spirit. This research is a qualitative research with a case study approach that was held in Satya Wacana Christian University (SWCU). This research concludes that the vision of creative minority is the university's vision to form leaders who drive the nation's development with the following skills and character: Leadership, creative, problem solver, critical mindfulness. This vision is manifested as points in the CPL study program. In addition, this vision is also integrated into the hidden curriculum through the process of: habituation, role models, internalization, and culturalization.